2014
DOI: 10.1038/ismej.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of polysaccharide utilization loci in the marine BacteroidetesGramella forsetii’ KT0803

Abstract: Members of the phylum Bacteroidetes are abundant in many marine ecosystems and are known to have a pivotal role in the mineralization of complex organic substrates such as polysaccharides and proteins. We studied the decomposition of the algal glycans laminarin and alginate by ‘Gramella forsetii' KT0803, a bacteroidetal isolate from North Sea surface waters. A combined application of isotope labeling, subcellular protein fractionation and quantitative proteomics revealed two large polysaccharide utilization lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
164
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(176 citation statements)
references
References 49 publications
9
164
1
2
Order By: Relevance
“…TBDR are important for microbial competition in the ocean, as cells with TBDR were observed to outcompete other microbes lacking TBDR in the presence of labile HMW-DOM released after a phytoplankton bloom in the North Sea (Teeling et al, 2012) and were also overexpressed in marine communities following HMW-DOM additions (McCarren et al, 2010). TBDR have been identified as important components of algal glycan utilization in Gramella forsetti, a widespread marine flavobacterium pivotal to remineralization of complex organic matter (Kabisch et al, 2014). However, it is unknown whether TBDR also assist in protein acquisition by marine microbes.…”
Section: Discussionmentioning
confidence: 99%
“…TBDR are important for microbial competition in the ocean, as cells with TBDR were observed to outcompete other microbes lacking TBDR in the presence of labile HMW-DOM released after a phytoplankton bloom in the North Sea (Teeling et al, 2012) and were also overexpressed in marine communities following HMW-DOM additions (McCarren et al, 2010). TBDR have been identified as important components of algal glycan utilization in Gramella forsetti, a widespread marine flavobacterium pivotal to remineralization of complex organic matter (Kabisch et al, 2014). However, it is unknown whether TBDR also assist in protein acquisition by marine microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Bacteroidetes bacteria are common in marine environments (791), abundant in organic particle-rich coastal waters (108,113,130,611,791), responsive to algal and jellyfish blooms (272,537,756,(791)(792)(793), copiotrophic (252), and prone to leading a surface-associated life (12,17,246,272,574,607) supported by the extracellular degradation of complex biopolymers such as polysaccharides and proteins (194,791,(794)(795)(796)(797). These bacteria harbor a large number of genes for adhesive exopolysaccharides, adhesion proteins, proteases, peptidases, glycoside hydrolases, and lipases, and several genes for biopolymer degradation are coregulated with the genes for TonBdependent transport systems (794,795,(798)(799)(800)(801)(802).…”
Section: Marine Bacteroidetesmentioning
confidence: 99%
“…Previous genome analysis has revealed that in Bacteroidetes, the polysaccharide degradation genes, including those encoding carbohydrate-active enzymes (CAZymes) and transporters, are frequently carried in large operons or regulon structures called PUL; these structures have been reported in many Bacteroidetes, from commensal bacteria of the human intestine to marine organisms (32,34,36,37). In short, PUL are clusters of coregulated genes or transcriptional units for polysaccharide degradation and related transportation.…”
mentioning
confidence: 99%
“…Detailed analyses of the genome structures of Algibacter species and their relationships with algal polysaccharides are rare. Also, in marine Bacteroidetes, many strains have been sequenced with draft or complete genomes, but only for a few strains in the family Flavobacteriaceae, including Zobellia galactanivorans (30,31), Gramella forsetii KT0803 (32,33), Formosa agariphila KMM 3901 T (34), and Polaribacter sp. strains…”
mentioning
confidence: 99%